2010
DOI: 10.3748/wjg.v16.i44.5565
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress sensitizes rats to pancreatitis induced by cerulein: Role of TNF-α

Abstract: In rats, chronic stress increases susceptibility for developing pancreatitis, which involves TNF-α sensitization of pancreatic acinar cells to undergo injury by physiological cerulein stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 54 publications
4
20
0
1
Order By: Relevance
“…Consistent with our finding, there are reports suggesting that stress can increase tumor growth and tumor marker expression [26,27]. It has also been shown that chronic stress increases susceptibility for developing pancreatitis in rats, which involves TNF-α (tumor necrosis factor-alpha) sensitization of pancreatic acinar cells to undergo injury [28]. However, in contrast to our finding there are studies indicating that chronic stress can strengthen the immune system [15], thereby may cause a resistance to tumorogenesis and forestall against elevating of serum tumor marker levels.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our finding, there are reports suggesting that stress can increase tumor growth and tumor marker expression [26,27]. It has also been shown that chronic stress increases susceptibility for developing pancreatitis in rats, which involves TNF-α (tumor necrosis factor-alpha) sensitization of pancreatic acinar cells to undergo injury [28]. However, in contrast to our finding there are studies indicating that chronic stress can strengthen the immune system [15], thereby may cause a resistance to tumorogenesis and forestall against elevating of serum tumor marker levels.…”
Section: Discussionsupporting
confidence: 92%
“…Lipase [LPS] is a pancreatic enzyme necessary for the absorption and digestion of nutrients that catalyzes the hydrolysis of glycerol esters of fatty acids. Estimation of LPS is used for diagnosis of pancreatic diseases such as acute and chronic pancreatitis and obstruction of the pancreatic duct [ 29 ]. Increased level of amylase and lipase were observed in the PCBs treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…This activity consumes high levels of ATP; failure to meet these energy demands can result in protein misfolding and endoplasmic reticulum stress responses. Changes in acinar cell ATP levels have been reported in experimental acute pancreatitis models (20,25), and the extent of ATP depletion in acute pancreatitis may correspond to disease severity (2). Whether such fluctuations in ATP levels influence AMPK activity in acute pancreatitis is unclear.…”
mentioning
confidence: 99%